2022
DOI: 10.3389/fendo.2022.992566
|View full text |Cite
|
Sign up to set email alerts
|

The associations between thyroid-related hormones and the risk of thyroid cancer: An overall and dose-response meta-analysis

Abstract: ObjectiveThyroid cancer (TC) is one of the most common malignant tumours of the endocrine system. Thyroid-stimulating hormone (TSH) is known as being a risk factor for TC, but other thyroid-related hormones are inconsistently associated with TC. The purpose of this study was to comprehensively evaluate the relationships between thyroid-related hormones and the risk of TC.MethodsThis study utilized searches of PubMed, Embase, Web of Science and Cochrane library up to the date of March 31st, 2022. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Many studies have shown the association of thyroid dysfunction with thyroid carcinoma as well as other cancer risks. [22][23][24] Although previous studies like a cohort study showed a link between subclinical hypothyroidism with an increased risk of thyroid cancer incidence. 25 On the other hand, previous results also revealed that untreated subclinical hypothyroidism may be associated with an increased risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the association of thyroid dysfunction with thyroid carcinoma as well as other cancer risks. [22][23][24] Although previous studies like a cohort study showed a link between subclinical hypothyroidism with an increased risk of thyroid cancer incidence. 25 On the other hand, previous results also revealed that untreated subclinical hypothyroidism may be associated with an increased risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have reported the association between thyroid hormones and PTC, 29–33 but no clear conclusions have been drawn. Higher FT4 levels were reported to be positively associated with thyroid cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Classical TSH actions are mainly mediated through the Gαs-adenylyl cyclase-protein kinase A-cyclic adenosine monophosphate pathway, which is associated with T4 and T3 production and thyrocyte proliferation. In this sense, several meta-analyses had associated higher serum TSH concentration with higher odds of TC [ 69 - 71 ].…”
Section: Probable Molecular Mechanisms Associated Between Ht and Dtcmentioning
confidence: 99%